Production Optimization and Cellulose System Characterization of Bacillus circulans Local Strain Using Inducer Avicel - Evi Susanti (Jurnal ILMU DASAR, 2011)
Exploration of aerobic bacteria which can produce cellulase system is very important to discover potential celulase resourse which can hydrolysis lignocelulose waste into glucose. The aimed of this researched were determine optimum condition of cellulase system production in Berg’s media with avicel as inducer and it’s characterization. Bacillus circulans local strain from laboratory of Microbiology ITB produced consist of CMC- ase(111.11U/mL)andavicelas (55.56U/mL) in Berg’s medium contain 0.5% avicel, pH=9.0 and 5 days of incubation. Characteristic of this cellulase system were: (1) optimum level of CMC-ase (129.97 U/mL) and avicelase (87.96 U/mL) was obtained at pH= 7.0, temperature 50oC and 2 hours incubation, (2) Vmaks and Km of CMC-ase was 1000 μg glucose/hour and 5%, Vmaks and Km of avicelase was 200 μg glucose/hour and 1.2%, (3) capable of hidrolizing sugarcane, corn cob and rice bran during optimum condition and released glucose 262 ppm, 81 ppm and 78 ppm. This research encouraged that Bacillus circulans capable of producing cellulose system with high activity and suggested to degradated lignocelluloses as feedstocks of bioetanol.